Red Ginger as a Potential SDG-3 Herbal Therapy: Molecular and Flow Cytometry Evaluation of CD4, CD8, and CD62L Lymphocyte Modulation in PCOS-Induced Rattus norvegicus - Siti Mudrikatin; Hany Puspita Aryani; Risha Setyowati (Jurnal Penelitian Pendidikan IPA, 2026)
Polycystic Ovary Syndrome (PCOS) is a highly prevalent endocrine disorder associated with hyperandrogenism, inflammation, and immune system dysfunction. Elevated levels of testosterone are known to affect lymphocyte profiles and contribute to the inflammatory processes in PCOS. The aim of this study was to evaluate the impact of red ginger extract (Zingiber officinale var. rubrum) on lymphocyte subpopulations in a testosterone-induced PCOS rat model. This experimental study involved 30 female Rattus norvegicus divided randomly into five groups: a normal control, a PCOS control (testosterone-induced without treatment), and three PCOS treatment groups receiving different doses of red ginger extract. PCOS induction was done using testosterone propionate. Following the treatment period, lymphocyte subpopulation analysis was performed using flow cytometry based on the CD4⁺, CD8⁺, and CD62L⁺ surface markers. The results indicated significant differences in the expression of CD4⁺, CD8⁺, and CD62L⁺ among all red ginger treatment groups compared to the PCOS control group (p < 0.05), suggesting an immunomodulatory effect of red ginger. In conclusion, the administration of red ginger extract was able to modulate the lymphocyte subpopulation profile in the PCOS model, potentially contributing to controlling immune responses associated with hyperandrogenism.